1035325 Analisis Faktor Penyebab Terjadinya Post Partum Blues dengan Skrining Edinburgh Postnatal Depression Scale (EPDS) - Adriani (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2019)
Abstract Changing the role of a woman into a mother is not always a pleasant thing for a married couple, sometimes conflicts occur both within the woman and conflict with her husband. If the attention to the psychological state of the post partum mother is lacking then it can cause the mother try to overcome the problem or the discomfort herself, this condition can cause the post partum mother to experience postpartum blues. In Indonesia, it is estimated that 50-70% of post-partum mothers experience postpartum blues on days 4-10. This research uses analytic survey with cross sectional research design, with a total sample of 160 people. Data were taken using a questionnaire which was displayed in a univariate and bivariate analysis using a SPSS computerized system. The results of the study are there is a relationship between maternal education (p 0.013), maternal occupation (p 0.013), husband support (p 0.021), family income (p 0,000) with post partum blues and there is no relationship between maternal parity (p 0.199), maternal age (p 0.391), and history of PMS (p 0.087) with post partum blues events. It is expected that researchers will be able to continue research with more variable variables and it is expected that health workers can improve services, especially in providing support to mothers during post partum period, thereby reducing the risk of mothers experiencing postpartum blues. Keywords: Postpartum blues, education, employment, husband support, PMS history